2023
DOI: 10.1007/s11356-023-26918-1
|View full text |Cite
|
Sign up to set email alerts
|

Residential houses — a major point source of microplastic pollution: insights on the various sources, their transport, transformation, and toxicity behaviour

Abstract: Municipal wastewater has been considered as one of the largest contributors and carriers of microplastics to the aquatic environment. However, the various residential activities that generate municipal wastewater are equally significant whenever the source of microplastics in aquatic system is accounted. However, so far, only municipal wastewater has received wide attention in previous review articles. Hence, this review article is written to address this gap by highlighting, firstly, the chances of microplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 136 publications
0
0
0
Order By: Relevance
“…Oni and Sanni [ 28 ] proposed that locations with elevated microplastic levels might be attributed to high population density and intense industrial activities, while areas with lower microplastic abundance could result from lower population densities and reduced industrial activities. Similarly, Jessieleenaet al [ 31 ] suggested that municipal wastewater, dependent on population and anthropogenic activities, is a major contributor to microplastics in aquatic environments. In contrast to other cities in Nigeria mentioned above, Birnin Kebbi is less populated and industrialized, potentially explaining its lower pollution levels.…”
Section: Discussionmentioning
confidence: 99%
“…Oni and Sanni [ 28 ] proposed that locations with elevated microplastic levels might be attributed to high population density and intense industrial activities, while areas with lower microplastic abundance could result from lower population densities and reduced industrial activities. Similarly, Jessieleenaet al [ 31 ] suggested that municipal wastewater, dependent on population and anthropogenic activities, is a major contributor to microplastics in aquatic environments. In contrast to other cities in Nigeria mentioned above, Birnin Kebbi is less populated and industrialized, potentially explaining its lower pollution levels.…”
Section: Discussionmentioning
confidence: 99%